Is feed-in-tariff policy effective for increasing deployment of renewable energy in Indonesia? - Dewi Yuliani (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
To accelerate the deployment of renewable energy technologies and to secure the electricity supply, the Government of Indonesia has issued several feed-in-tariff regulations for various renewable energy sources, which were previously predominated by pilot projects using government funding. The feed-in tariff is a policy instrument that has been successfully applied in many other countries to support renewable electricity, and it is known for its simplicity in implementation. This study undertakes exploratory research to evaluate how the policy works in Indonesia, not only as stated in official reports, but also in the field. The study's results show that while the policy triggers investment interest in renewable power plants, there are many obstacles encountered at the deployment stage due to imperfections in the feed-in-tariff policy package and some non-cost factors. In addition, several unanticipated side effects were identified at the local level as a consequence of the upturn in investment interest. The study indicates that the transition to cleaner energy is much more challenging for developing countries such as Indonesia.
Keywords: O13; Q43; 330; feed-in-tariff policy; renewable energy; deployment